59.1: Invited Paper: Flexible Flat‐Panel Display Designs with Gate Driver Circuits Integrated within the Pixel Area. Issue 1 (June 2015) - Yoshida, Hidefumi; Tanaka, Kohei; Noma, Takeshi; Nishiyama, Takayuki; Yonebayashi, Ryo; Nasu, Yasuhiro; Ishida, Takeshi; Murata, Mitsuhiro; Nakanishi, Yohei; Kadowaki, Shinya; Watanabe, Hisashi; Tomotoshi, Takuma; et al.
Abstract : We have developed a new stylish TFT‐LCD. We located gatedriver monolithic circuits in the pixel area. As there are no electronic circuits in the frame area, we can realize a narrow border and round corners or a multi‐concave shape, and the frame shape can be easily revised.